HUBUNGAN ANTARA STATUS GIZI MASA LALU ANAK DAN PARTISIPASI IBU DI POSYANDU DENGAN KEJADIAN TUBERKULOSIS PADA MURID TAMAN KANAK KANAK - Siti Madanijah; Nina Triana (Food and Nutrition Society of Indonesia, 2007)
The Tuberculosis (TB) was detected on kindergarten students is triggered by the poor past nutritional status. The best way to maintain health and nutritional status can be accomplished at posyandu. The objective of this study is to analyze the correlation between children past nutritional status and mother’s participation at posyandu with TB case on kindergarten students. The research was designed by cross sectional study with purposive method. This research had been conducted at Kecamatan Paseh, Kabupaten Sumedang, West Java from January to May 2006. The samples consisted of 30 kindergarten students suffered from TB and 30 healthy students that were selected randomly. The differences between the two groups were analyzed with the t-test and Mann Whitney test. The influenced variables were analyzed with multiple regression tests. Related with past nutritional status, on the TB group, 16.6% of the samples had moderate and severe malnutrition, while severe malnutrition was not found on the other group. The participation of mothers were less categories on the TB group, as much as 56.7%, compared to the group with no TB (26.7%). There were significant correlation between children past nutritional status and mothers’ participation at posyandu with the TB case.